Characteristics and Specialist Linkage to Care of Patients Diagnosed With Chronic Hepatitis C Across Different Settings in an Urban Academic Hospital: Implications for Improving Diagnosis and Linkage to Care - Im, Dan C. S.; Reddy, Susheel; Hawkins, Claudia; Galvin, Shannon (Frontiers in Microbiology, 2021)
Introduction: Chronic hepatitis C virus (HCV) infection is a significant public health problem. Strategies to identify more HCV infections and improve linkage to care (LTC) are needed. We compared characteristics, treatment and LTC among chronic HCV patients in different health care settings. Methods: Newly diagnosed HCV antibody positive (anti-HCV+) patients within settings of acute care, inpatient and outpatient in one health system were studied. Proportion of LTC and treatment were analyzed only for HCV RNA positive patients. Chi-square, one-way ANOVA and logistic regression were used to compare the characteristics and outcomes in the three care settings. Patients in acute care settings were excluded from multivariate analyses due to low sample size. Results: 43, 368 and 1159 anti-HCV+ individuals were identified in acute care, inpatient and outpatient respectively. Proportion of RNA positivity in acute, inpatient and outpatient were 47.8%, 60.3% and 29.2% respectively (p < 0.01). After adjusting for age, insurance type, race, and gender, outpatients had higher odds of LTC and of treatment (OR 4.7 [2.9, 7.6] and 4.5 [2.8, 7.3]). Conclusions: Inpatients had lower proportion of LTC and treatment compared to outpatients. Use of LTC coordinators and the provision of integrated service for specialty care may improve outcomes.